The Effectiveness Of Table-Top Exercise Simulation For Hospital Disaster Preparedness Training A Systematic Review - Mutiarasari, Diah; Zulkifli, Andi; Rivai, Fridawaty; Thamrin, Yahya; Mallongi, Anwar; Miranti, Miranti (Journal of Neonatal Surgery, 2025)
Background: To improve the knowledge and skills of hospital staff and better equip them to the handle unforeseen emergencies, hospitals in Indonesia need a participatory disaster preparedness training model. Media used is a simulation of the tabletop exercise model with the collaborative method using a disaster scenario. This study aims to determine whether current research adequately conceptualizes, describes, and interprets tabletop exercise related to hospital disaster preparedness to account for the effectiveness of the simulations. Method: This systematic review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Six electronic databases were used as sources of information: google scholar, cambridge core, pubmed, proquest, scopus, and science direct. The search terms were "simulation" (tabletop exercise simulation or simulation-based disaster) and "hospital disaster preparedness". Results: Of the 470 research studies found during the search phase, six met the requirrements to be included in this review. The included six studies showed that tabletop exercise could improve the knowledge and skills of officers in disaster management in hospitals. Conclusion: Tabletop exercise can help hospital officials become more knowledgeable and competent in crisis management. This tabletop exercise is a creative and useful training tool for hospital disaster preparedness.